OVERVIEW OF LEARNING CONCEPTS - Rizki Syafitri; Neviyarni (Literasi Nusantara, 2021)
In the article analyzing this concept learning uses a trusted literature review, from learning concepts which are the basis for giving a label and category to something that refers to a set of forms or attributes that already have one and more properties together associated with one rule. The material of this article was taught by lecturer Neviarni who came from the FIP Counseling Guidance, Padang State University.